2005
DOI: 10.1128/aem.71.11.7041-7052.2005
|View full text |Cite
|
Sign up to set email alerts
|

European Origin of Bradyrhizobium Populations Infecting Lupins and Serradella in Soils of Western Australia and South Africa

Abstract: We applied a multilocus phylogenetic approach to elucidate the origin of serradella and lupin Bradyrhizobium strains that persist in soils of Western Australia and South Africa. The selected strains belonged to different randomly amplified polymorphic DNA (RAPD)-PCR clusters that were distinct from RAPD clusters of applied inoculant strains. Phylogenetic analyses were performed with nodulation genes (nodA, nodZ, nolL, noeI), housekeeping genes (dnaK, recA, glnII, atpD), and 16S-23S rRNA intergenic transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 45 publications
14
124
2
Order By: Relevance
“…According to the phylogeny of the concatenated dataset, we propose that USDA strains 3063, 3717, 3043 and 3057a should be considered for reclassification. Also, despite evidence that lupines are mainly nodulated by members of the genus Bradyrhizobium [3], the two strains isolated from lupines in this study were shown to be Burkholderia sp. and Rhizobium sp.…”
Section: Resultscontrasting
confidence: 84%
“…According to the phylogeny of the concatenated dataset, we propose that USDA strains 3063, 3717, 3043 and 3057a should be considered for reclassification. Also, despite evidence that lupines are mainly nodulated by members of the genus Bradyrhizobium [3], the two strains isolated from lupines in this study were shown to be Burkholderia sp. and Rhizobium sp.…”
Section: Resultscontrasting
confidence: 84%
“…Topological incongruence among the phylogenetic trees of different marker genes of a single strain is not uncommon, 48,49,54) and such incongruence of topologies based on GlnII and RecA of bradyrhizobial strains have also been reported by other authors. 9) In the GyrB-tree (Fig.…”
Section: Strain Ek05mentioning
confidence: 53%
“…Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101]. There is an agreement, that (a) in numerous cases the world distribution of microsymbiont strains followed the distribution of their hosts, and the symbiosis-associated part of the genome (localized on symbiotic plasmid or symbiotic island) was subjected to the most intense evolution and fitting [103,104,106,107], and (b) other (non-symbiotic) parts of the rhizobial genome changed together with the symbiosis-related regions [105,108]. Genetic analyses of microsymbiont populations isolated from different but closely related legumes support the hypothesis of coevolution in Rhizobium-legume symbiosis, which takes place in centers of genetic diversification of plant hosts [109][110][111].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%